(untitled) (Journal of the College of Basic Education, 2022)
The study dealt with estimating the volume of eroded soils in Wadi Sir Khatun by applying the EPM model, and this model is one of the mathematical methods by which it is possible to estimate the amount of sediment and determine the severity of water erosion in the parts of the basin that may be threatened by erosion. and soil protection, vegetation cover, precipitation, and heat), and by employing the applications of modern technologies by integrating indicators to estimate the potential water erosion coefficient of soils, the EPM model GavrilovicSolobodan has become the approved model for estimating soil erosion and its sediment yield in most countries, the study showed that (66%) of The basin parts fall within the fifth and sixth degrees, which represent the high and very high category of erosion. The results also showed that the factors of rainfall and topography, which include (slope degree, slope shape and ground system) effectively contribute to the occurrence of water erosion.problem of water erosion.